2022
DOI: 10.1136/bmjopen-2021-054658
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in bodyweight change following COVID-19 lockdown measures in the Netherlands: a prospective longitudinal study

Abstract: BackgroundThe current study aimed to prospectively assess bodyweight change following the implementation of lockdown measures to contain the COVID-19 pandemic in the Netherlands and to explore the potentially moderating role of gender in this association.DesignUsing Dutch DNB Household Survey panel data collected between 1993 and 2020, we estimated fixed-effects regression models of bodyweight change. Models were stratified by gender and formal tests of gender differences in coefficient estimates were performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…On the other hand, no consistent results have been reported on the association between weight gain and sex differences. Some studies reported no sex differences [13,14], others reported significantly greater weight gain in women [11,12,[15][16][17], and still others reported significantly greater weight gain in obese adolescents and children than in men [18,19]. The variation in these results may be due to differences in age, race, education level, and other factors.…”
Section: Discussionmentioning
confidence: 95%
“…On the other hand, no consistent results have been reported on the association between weight gain and sex differences. Some studies reported no sex differences [13,14], others reported significantly greater weight gain in women [11,12,[15][16][17], and still others reported significantly greater weight gain in obese adolescents and children than in men [18,19]. The variation in these results may be due to differences in age, race, education level, and other factors.…”
Section: Discussionmentioning
confidence: 95%
“…We flagged reported bodyweights lower than 25 kg or greater than 250 kg, reported heights lower than 100 cm or greater than 240 cm, or BMI scores lower than 14 kg/m 2 or greater than 55 kg/m 2 as implausible (cf. Flegal et al, 2019 , van den Broek and Fleischmann, 2022 ), and excluded respondents with such scores.…”
Section: Methodsmentioning
confidence: 99%